A Descriptive Cross-Sectional Study to Assess the Knowledge and Practice of Antenatal Mothers Regarding Maternal Diet Including Macronutrients and Micronutrients in Selected Hospitals of Indore (M.P.) in the Year 2022–2023 - Rakhi Chandel; Hephziba Elza Biju; Anusha Joseph; Vinti Arther; Megha Lawrence; Preeti Sawner; Shefali Narware; Aarti Khede (International Journal of Women's Health Nursing And Practices, 2026)
A balanced and adequate diet is most important during pregnancy to meet the mother's increased needs and prevent nutritional stress. Maternal nutrition during pregnancy plays a crucial role in lowering both maternal and infant mortality rates. This study aimed to evaluate the level of knowledge and the dietary practices of antenatal mothers concerning maternal nutrition, including both macronutrients and micronutrients. A descriptive cross-sectional research design was used, involving 100 pregnant women selected through a purposive sampling method. Data were gathered using a self-developed knowledge questionnaire along with a practice checklist. The results indicated that out of the 100 antenatal mothers, 84% demonstrated an average level of knowledge about maternal nutrition, 12% had poor knowledge, and only 4% showed good knowledge regarding dietary requirements during pregnancy, including macronutrient and micronutrients. In terms of dietary practices, the findings revealed that 54% of the participants followed good dietary practices, 44% had fair practices, and only 2% exhibited poor dietary practices during pregnancy. Furthermore, the analysis showed a statistically significant association between the mothers’ occupation and the number of children they had with their level of knowledge about maternal diet. (X²=18.444(p<0.05), and X² =15.940(p<0.05) respectively). The correlation between knowledge score and practice score is 0.203916, which indicates a low positive correlation. The study concluded that the practice of antenatal mothers is good, but the knowledge score is average, and there could be many reasons for good practices, but due to a lack of knowledge, public perception is limited. Therefore, community nutritional education and antenatal nutritional counseling need to be strengthened in remote areas.
Keywords: Pregnancy; antenatal mothers; counseling; macronutrients; micronutrients